Treatment of Dry Eye Disease (DED) in Asia: Strategies for Short Tear Film Breakup Time-Type DED - Atsushi Kawahara (MDPI AG, 2023)
Dry eye disease (DED) is a multifactorial disorder in which tear fluid homeostasis is lost, resulting in increased tear film osmolarity and ocular surface irritation. In Asia, the short tear film breakup time-type DED, which has become a global problem in recent years, is common. While the mainstay of DED treatment in the West is the suppression of inflammation, the first goal of treatment is the stabilization of the tear film in Asia. To date, artificial tears and steroid eye drops have been the main treatment for DED. However, artificial tears require frequent administration of eye drops and thus pose adherence problems, while steroids have problems with side-effects (cataracts, increased intraocular pressure). This review evaluates the new generation therapies in Asia based on what is known about them and demonstrates that they are more effective for DED than traditional therapies such as artificial tears and steroids. Based on considerations, it is proposed that the optimal treatment for the short tear film breakup time-type DED is the initial application of mucin-secretion-enhancing eye drops (long-acting diquafosol) and oral supplements; and if additional treatment is needed, cyclosporine eye drops and the adjunctive therapies presented in this review are added.